Gezer VI : the objects from Phases I and II (1964-1974) - Gilmour, Garth Hugh (Annual of the Hebrew Union College/Nelson Glueck School of Biblical Archaeology, 2014)
With the exception of objects previously published in Gezer V, Gezer VI provides a comprehensive database with listings of all of the objects recovered during both the Phase I (1968-1971) and Phase II (1971-1974) HUC excavations at the site. In addition, the volume offers a summary of the stratigraphic history of Tell Gezer and includes a series of plates illustrating a large sample of the finds sorted by type and strata. Provided also are a series of comparative studies of the major material and type groupings of the object repertoire.